Enhancement of hydrocarbons and phenols in catalytic pyrolysis bio-oil by employing aluminum hydroxide nanoparticle based spent adsorbent derived catalysts. (January 2022) - Gupta, Shubhi; Lanjewar, Rahul; Mondal, Prasenjit
Abstract: The present study investigated the effects of metal loaded spent adsorbent as catalyst for the catalytic pyrolysis of pine needle biomass. Metal active sites (Ni, Fe, Cu, Zn and Mo) were introduced in alumina matrix by wet impregnation process. Non-catalytic and catalytic semi-batch pyrolysis study was carried out at conditions: 550 °C temperature, 50 °C min −1 heating rate and 200 mL min −1 N2 flow rate. Results indicated significant deoxygenation potential 3.33–35.57% of the applied catalysts towards oxygenated compounds by converting them into their corresponding hydrocarbon (27.70–36.41%) and phenolic (40.41–46.04%) derivatives. Among all the catalysts, Ni/Al and Fe/Al produced the highest quality bio-oil by enriching their carbon content to 62.93 and 60.14% and heating value to 31.41 and 26.86 MJ kg −1, respectively. Moreover, significant enhancement in their hydrocarbons (36.41 and 36.01% for Ni/Al and Fe/Al, respectively) and phenolic compounds (46.04 and 41.67% for Ni/Al and Fe/Al, respectively) from 9.15% hydrocarbons and 13.32% phenols in non-catalytic bio-oil had also been observed. Presence of CO and CO2 in the evolved gases also represented the occurrence of deoxygenation reactions during catalytic breakdown. Hydrocarbon and phenol-rich bio-oil can find its application either as a replacement for petroleum fuel or an industrial-grade chemical. Thus, catalysts derived from spent aluminum hydroxide nanoparticle adsorbent can act as an effective substitute for the currently utilized high-cost catalysts in catalytic pyrolysis of biomass. Graphical abstract: Image 1 Highlights: Spent AHNP adsorbent had been utilized as catalyst in catalytic pyrolysis. Ni/Al showed highest bio-oil deoxygenation potential of 35.57%. Catalytic bio-oil mostly contained hydrocarbons, phenols and methyl phenols. Catalytic performance was highly dependent on metal-support interaction. Enhancement in bio-oils' application towards fuel and chemical recovery option.